Risk Factors for Underreporting of Life-Limiting Comorbidity Among Adults With Lower-Limb Loss - Samantha Jeanne Stauffer CPO, MSOP; Mayank Seth PhD; Ryan Todd Pohlig PhD; Emma Haldane Beisheim-Ryan PT, DPT, PhD; John Robert Horne CPO; Sarah Carolyn Smith PT, DPT; Frank Bernard Sarlo MD; Jaclyn Megan Sions PT, DPT, PhD (SAGE Publishing, 2023)
Peripheral neuropathy (PN) and peripheral arterial disease (PAD) are life-limiting comorbidities among adults with lower-limb loss that may not be adequately addressed in current care models. The objective of this study was to evaluate underreporting of PN and PAD among adults with lower-limb loss. We conducted a secondary analysis of a cross-sectional dataset of community-dwelling adults with unilateral lower-limb loss seen in an outpatient Limb Loss Clinic (n = 196; mean age = 56.7 ± 14.4 years; 73.5% male). Individuals participated in standardized clinical examinations including Semmes-Weinstein monofilament testing to assess for PN and pedal pulse palpation to assess for PAD. Bivariate regression was performed to identify key variables for subsequent stepwise logistic regression to discern risk factors. Clinical examination results indicated 16.8% (n = 33) of participants had suspected PN alone, 15.8% (n = 31) had suspected PAD alone, and 23.0% (n = 45) had suspected PN and PAD. More than half of participants with clinical examination findings of PN or PAD failed to self-report the condition (57.7% and 86.8%, respectively). Among adults with lower-limb loss with suspected PN, participants with dysvascular amputations were at lower risk of underreporting (odds ratio [OR] = 0.2, 95% CI: 0.1-0.6). For those with suspected PAD, those who reported more medication prescriptions were at lower risk of underreporting (OR = 0.8, 95% CI: 0.7-1.0). Adults with lower-limb loss underreport PN and PAD per a medical history checklist, which may indicate underdiagnosis or lack of patient awareness. Routine assessment is highly recommended in this population and may be especially critical among individuals with non-dysvascular etiology.